N′-(4-Chlorobenzylidene)-2-hydroxybenzohydrazide - Zhang, Shu-Ping (International Union of Crystallography, 2008)
The title molecule, C(14)H(11)ClN(2)O(2), adopts a trans configuration with respect to the C=N double bond. An intramolecular N—H⋯O hydrogen bond contributes to molecular conformation and the two benzene rings form a dihedral angle of 17.9 (8)°. In the crystal structure, intermolecular O—H⋯O hydrogen bonds link the molecules into chains running along [10[Image: see text]].